Literature Review on Football Learning Strategies for Student Competency Development - Musfira, Nurul; Bismar, Ahmad Rum (Sains Global Institut, Indonesia, 2025)
This literature review explores contemporary football learning strategies and their effectiveness in enhancing student competencies, including technical skills, tactical understanding, cognitive development, and social behavior. Drawing on 30 peer-reviewed journal articles published within the last ten years, the review categorizes the learning strategies into eight models: Play-Teach-Play (PTP), Reciprocal Learning, Teaching Games for Understanding (TGfU), Problem-Based Learning (PBL), Drill Method, Sport Education Model (SEM), Differentiated Instruction (DI), and Cooperative Learning. The findings reveal that student-centered models generally yield greater competency development than traditional direct instruction. For example, Karisman et al. (2024) demonstrated a significant improvement in technical abilities using the PTP model, with GPAI scores rising from 53.20 to 78.65 among students aged 6–9. Syahruddin (2023) applied the Reciprocal Learning model, resulting in passing technique scores increasing from 7.86 (pre-test) to 27.38 (post-test). Additionally, Zanuarta and Priambodo (2024) found that PBL improved student motivation scores from 3.5 to 4.2 (on a 5-point scale), although cognitive score gains were modest. TGfU was especially effective in developing tactical awareness and decision-making skills. The review concludes that hybrid and student-centered instructional designs—particularly TGfU, SEM, and PBL—are most effective for developing holistic football competencies in educational settings. Recommendations are made for future longitudinal and mixed-methods studies to examine the sustainability and contextual adaptability of these approaches